Signifying software engineering to computational thinking learners with AgentSheets and PoliFacets. (June 2017) - Monteiro, Ingrid Teixeira; Salgado, Luciana Cardoso de Castro; Mota, Marcelle Pereira; Sampaio, Andréia Libório; de Souza, Clarisse Sieckenius
Abstract: Nonprofessional end user programs have increased remarkably in volume and diversity. However, for such programs to be usable and reliable, their creators should be familiar with software engineering practices that are typically not part of their range of competence and source of enjoyment. While the expansion of computational thinking acquisition (CTA) initiatives at schools and the availability of improved programming environments have contributed to facilitate the learners' coding tasks, much less has been done to facilitate the acquisition of software quality notions. This paper reports on a Brazilian CTA program guided by semiotic principles and describes a study of how the technology used in it prefigures elements of software engineering in the participants' programs created with AgentSheets. Our research contributions touch on the semiotic potential of CTA infrastructures and on associated pedagogical considerations for expanding CTA programs with software engineering basics. We also propose items for an interdisciplinary research agenda.